2007
DOI: 10.1021/bi061917z
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Sugar Transport by Rabbit SGLT1:  Single-Molecule Atomic Force Microscopy versus Transport Studies

Abstract: In the apical membrane of epithelial cells from the small intestine and the kidney, the high-affinity Na+/d-glucose cotransporter SGLT1 plays a crucial role in selective sugar absorption and reabsorption. How sugars are selected at the molecular level is, however, poorly understood. Here atomic force microscopy (AFM) was employed to investigate the substrate specificity of rbSGLT1 on the single-molecule level, while competitive-uptake assays with isotope-labeled sugars were performed in the study of the stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Stereospecificity of interactions between extracellularly located parts of the whole SGLT1 and glucose has been shown previously (10). For example, the binding probability of 1-thio-␤-D-glucose, coupled to the flexible cross-linker on an atomic force microscopy tip by a thio-glycosidic bond at the sugar's C1 position, was decreased significantly if (in the presence of sodium) free D-glucose was applied during force distance cycles using SGLT1-transfected Chinese hamster ovary cells, whereas only a slight effect could be observed in the presence of L-glu- Table 3.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Stereospecificity of interactions between extracellularly located parts of the whole SGLT1 and glucose has been shown previously (10). For example, the binding probability of 1-thio-␤-D-glucose, coupled to the flexible cross-linker on an atomic force microscopy tip by a thio-glycosidic bond at the sugar's C1 position, was decreased significantly if (in the presence of sodium) free D-glucose was applied during force distance cycles using SGLT1-transfected Chinese hamster ovary cells, whereas only a slight effect could be observed in the presence of L-glu- Table 3.…”
Section: Discussionmentioning
confidence: 54%
“…4 and 8) and functional asymmetry (sugar selectivity seems to be different between the extracellular and the cytoplasmic face) (9). Recently we have shown that there are at least two sugar interaction sites on rabbit SGLT1, one representing the initial binding site and one related to the translocation pathway (10). SGLT1 can be inhibited by several glucosides with either aromatic or aliphatic aglucone residues (11,12).…”
mentioning
confidence: 99%
“…New SGLT1 Sensors-In the current study new coupling chemistry for tethering thioglucose, hexyl-glucose, and aminophlorizin to the AFM tip was developed. Previously, AFM studies on SGLT1 had been performed mainly with a vinylsulfone linker between the PEG chain and thioglucose or a modified 3Ј aminophlorizin (19,20,48). By using acrylamide as the thioreactive group to attach thioglucose to PEG 5000 , the size (and charge) of the thioester linkage is reduced compared with vinylsulfone-PEG 800.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be assumed that at 37°C some of the primarily not accessible binding sites further down in the translocation pathway are reached by thioglucose on AA-PEG 5000 (21). A sequential multistep mechanism for sugar recognition and translocation has also been proposed based on prior AFM investigations (20).…”
Section: Sglt1 Sensorsmentioning
confidence: 99%
See 1 more Smart Citation